1998
DOI: 10.1034/j.1600-0420.1998.760513.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative measurements of macular hole with scanning laser ophthalmoscopy. Correlation with functional outcome

Abstract: ABSTRACT.Purpose: To measure the dimensions of macular holes before surgery and compare them with the functional outcome. Methods: A prospective study of ten consecutive patients scheduled for macular hole surgery. Macular holes were imaged with scanning laser ophthalmoscopy with different laser wavelengths. Computerized image analyses were used to measure the size of the hole and the surrounding rim. Results: Eyes were referred to three different groups preoperatively according to visual function. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Analysis of macular microperimetry showed in previous studies15 2428 that eyes with open macular holes have an absolute scotoma that corresponds to the neurosensory defect as well as a surrounding relative scotoma that corresponds to the surrounding neurosensory retinal detachment. These studies found that the size of the absolute scotomata correspond to the best-corrected visual acuity.…”
Section: Discussionmentioning
confidence: 97%
“…Analysis of macular microperimetry showed in previous studies15 2428 that eyes with open macular holes have an absolute scotoma that corresponds to the neurosensory defect as well as a surrounding relative scotoma that corresponds to the surrounding neurosensory retinal detachment. These studies found that the size of the absolute scotomata correspond to the best-corrected visual acuity.…”
Section: Discussionmentioning
confidence: 97%
“…Traditionally, MH size had been estimated based on biomicroscopic observation or photographic evaluation. As imaging technology developed and became applicable to fundus assessment, more attempts were made to measure MH size precisely [54,55]. In 2002, Ip et al [56] first used optical coherence tomography (OCT), the most common method used today, to quantify MH size.…”
Section: Preoperative Predictive Factorsmentioning
confidence: 99%
“…This fi nding suggests that pathologic lipofuscin accumulation in the RPE surrounding areas of GA has reduced retinal sensitivity as functional correlate. In postmortem specimens obtained from patients with GA due to AMD, a linear relationship between the loss of RPE and choriocapillaris atrophy has been observed [ 66 ]. But reduced retinal sensitivity may directly depend on alterations in photoreceptor (PR) function along the border of GA as recently hypothesized by Bearelly et al [ 49 ].…”
Section: Integrating Morphology and Function In Geographic Atrophymentioning
confidence: 92%
“…Schmitz-Valckenberg et al, using SLO microperimetry, found reduced retinal sensitivity in the areas of increased FAF bordering GA compared to areas with normal FAF [ 65 ]. The fi rst one is that RPE atrophy causes secondary choriocapillaris loss and PR degeneration [ 66 ]. Preliminary data also suggest that NIR-FAF better correlates to retinal sensitivity changes compared to SW-FAF [ 14 , 16 ].…”
Section: Integrating Morphology and Function In Geographic Atrophymentioning
confidence: 99%